The Officer Cavalry School Library: history and book collections composition - A. M. Panchenko (Библиосфера, 2017)
In article presents a brief history of creating the Officer Cavalry School, regulatory frameworks of it and its libraries. It analyzes «Theses on the Officer Cavalry School» of 1887, 1893 and 1898, concerning activities of its book collection, «Rules to use the Officer Cavalry School Library» stated in «Charter of meetings of Officer Cavalry School» (1887), as well as in printing «Catalog of the Officer Cavalry School Library» (1894) and the 1st addition to it (1895), «Catalog…» (1899) and the 1st addition to it (1902) compiled by the librarian, Colonel L. V. De-Witt. Features of using books and periodicals from the library and its reading room are fixed for the constant and variable structures of the school.